Implementation of the Cleanliness, Health, Safety, and Environmental Sustainability (CHSE) Health Protocol in the Tourism Industry in Balige City, Toba Regency - Rahmat Darmawan (Politeknik Pariwisata Medan, 2021)
The application of the CHSE health protocol (Prokes) in tourist destinations should be investigated in an effort to ensure the tourism industries in Balige City and its surroundings are ready to accept tourist visits during a pandemic or new normal. The purpose of this study is to explore the application of the CHSE program to the tourism industry as an effort to build tourist trust to visit and settle in Toba Regency. This research is entitled to examine the application of the CHSE program in the tourism industry including hotels, restaurants/cafe/canteens, souvenir shops and tourist attractions. This study uses a qualitative design with qualitative descriptive data analysis. The data grouping was carried out using the ethnographic method of the Spradley Model (1980). The informants taken are key informants including tourism industry managers/tourists and tourists as the main informants. Based on the analysis of the problem with a qualitative approach, several conclusions can be drawn as follows. First, the realization of the implementation of the CHSE process was concluded to be poor, especially the realization in tourist objects, / restaurants / restaurants managed by amateurs / local communities. Nevertheless, the realization of the implementation of the CHSE process looks optimal in the tourism industry which is managed professionally/management. Furthermore, it was concluded that the response of tourists to the condition of the health program and the implementation of the CHSE program was not good, especially in the tourism industry which was managed by the local community.